Кримінальна відповідальність за постановлення суддею (суддями) завідомо неправосудного вироку, рішення, ухвали або постанови - Нос, Степан Петрович (Національний університет "Львівська політехніка", 2021)
В роботі на підставі вивчення наукової літератури, законодавчих, інших нормативно-правових актів та судової практики здійснено системний аналіз питання кримінальної відповідальності за постановлення суддею (суддями) завідомо неправосудного вироку, рішення, ухвали або постанови. Під родовим об’єктом досліджуваного кримінального правопорушення потрібно вважати правосуддя, основним безпосереднім об’єктом – правосуддя в частині забезпечення права на постановлення судом правосудного рішення, предметом – будь-яке судове рішення, в тому числі й висновки та рішення Конституційного Суду України. З об’єктивної сторони кримінальне правопорушення, передбачене ч. 1 ст. 375 КК України є кримінальним правопорушенням із формальним складом, а передбачене ч. 2 ст. 375 КК України – кримінальним правопорушенням із матеріальним складом, оскільки передбачає обов’язкове настання тяжких наслідків. Суб’єктами кримінального правопорушення, передбаченого ст. 375 КК України можуть бути судді судів загальної юрисдикції, судді Конституційного Суду України та присяжні. З суб’єктивної сторони – це діяння вчиняється виключно з прямим умислом. Висловлено пропозиції щодо вдосконалення змісту ст. 375 КК України, а також щодо необхідності доповнення Кримінальний кодекс України ст. 375-1 «Прийняття третейським суддею (суддями) завідомо незаконного рішення». В работе на основе изучения научной литературы, законодательных и других нормативно-правовых актов и судебной практики осуществлен системный анализ вопросов уголовной ответственности за вынесение судьей (судьями) заведомо неправосудного приговора, решения, определения или постановления. Под родовым объектом исследуемого уголовного преступления следует считать правосудие, основным непосредственным объектом – правосудие в части обеспечения права на постановления судом правосудного решения, предметом – любое судебное решение в том числе выводы и решения Конституционного Суда Украины. С объективной стороны уголовное правонарушение, предусмотренное ч. 1 ст. 375 УК Украины является уголовным правонарушением с формальным составом, а предусмотренное ч. 2 ст. 375 УК Украины – уголовным правонарушением с материальным составом, поскольку предусматривает обязательное наступление тяжких последствий. Субъектами уголовного правонарушения, предусмотренного ст. 375 УК Украины могут быть судьи судов общей юрисдикции, судьи Конституционного Суда Украины и присяжные. С субъективной стороны это деяние совершается исключительно с прямым умыслом. Высказаны предложения по совершенствованию содержания ст. 375 УК Украины, а также о необходимости дополнения УК Украины ст. 375-1 «Принятие третейским судьей (судьями) заведомо незаконного решения». The paper provides system-based analysis of the issue of criminal liability for delivering knowingly unfair sentence, judgment, ruling or order by the judge (judges) based on the study of academic literature, legislative acts, other regulations, and case law. It has been proved that although criminal liability for unjust (dishonest) judgment of persons authorized to administer justice has been historically inherent in national law since ancient times, a separate norm that would provide punishment for delivering unfair judgment appeared only in the Hungarian Criminal Code in 1789. Historical and legal research shows that in the sources of criminal law being in force on the territory of Ukraine there was a rather clear system of crimes, which today are covered by the concept of “delivery of unfair court judgment”. That system was built taking into consideration the manner of proceeding (civil or criminal), the substance of the judgment delivered by the judge (improvement or deterioration of the convict’s position). The study of foreign Criminal Codes led to the conclusion that the Criminal Codes of foreign countries traditionally make use of two approaches towards the norm attracting criminal liability of the judge for delivering unjust judgment: 1) the relevant provision is contained in the structural part of the Criminal Code, which directly relates to criminal liability for crimes against justice; 2) liability for such acts arises according to the norms that establish liability for official crimes. Justice should be considered as the generic object of the criminal offence under study; the main direct object is justice with regard to ensuring the right to fair judgment in court; the subject is any court judgment including conclusions and judgments of the Constitutional Court of Ukraine. Since the Constitution of Ukraine clearly states that justice in our country is administered only by courts, justice should be regarded as law enforcement activities of the court in terms of consideration and resolution of civil, criminal, commercial and administrative cases in the procedural order prescribed by the law to protect human and citizen rights and freedoms, the rights and legitimate interests of legal entities and the state interests. Objectively, the criminal offence covered by paragraph 1, Article 375 of the Criminal Code of Ukraine is a formally defined crime, while the criminal offence covered by paragraph 2, Article 375 of the Criminal Code of Ukraine is a materially defined crime as it necessarily causes heavy consequences. The delivery of the court decision has the following stages: drawing up, signing and announcing the respective judicial act. The moment when there is an absence of the elements of criminal offence covered by Article 375 of the Criminal Code of Ukraine is the moment of proclamation of the operative part of the judgment. However, the following circumstances of the case should be taken into consideration when we speak of the termination of certain criminal offence covered by Article 375 of the Criminal Code of Ukraine: manner of proceeding (as a matter of fact, in civic, commercial or administrative proceedings, only introductory and operative parts may be proclaimed, whereas in criminal proceedings – the sentence is read out as a whole); peculiarities of legal proceedings (written proceedings, summary procedure); presence or absence of the parties. The judges of the Courts of General Jurisdiction, the judges of the Constitutional Court of Ukraine and the jury may be the subjects of the criminal offence under Article 375 of the Criminal Code of Ukraine. From the subjective aspect, this act is done exclusively willfully and knowingly. It has been proved that the actions of an incompetent judge to make an unfair court judgment may fall under the Article 375 of the Criminal Code of Ukraine only in those cases when, in addition to being aware of his/her incompetence, he/she was also aware of the fact of making a knowingly unfair sentence, judgment, ruling or order. If there are no elements of advance awareness, precise understanding of the illegality of the decision made, then there is an absence of crime in the act under the Article 375 of the Criminal Code of Ukraine because there is no evidence of subjective aspects of the given criminal offence. It has been proved that it is inexpedient to institute criminal proceedings against the judge for negligent delivery of judgment because: the judge may be subject to disciplinary responsibility for delivering unlawful court judgment; the establishment of such liability will complicate the distinction between criminal acts and different understanding and interpretation of vaguely worded legal provisions; the establishment of such criminal liability would be an example of excessive criminalization. Delivery of knowingly unfair sentence, judgment, ruling or order should be clearly distinguished from miscarriage of justice, which is unintentional. Making an illegal decision due to miscarriage of justice usually entails disciplinary actions against the judge. In the sanctions of Part 1 and Part 2 of Art. 375 of the Criminal Code of Ukraine it is not expedient to carry the punishment in the form of a fine as an alternative punishment, as it is unlikely to achieve the main purpose of punishment – correction of a person. As a mandatory additional punishment, it would be appropriate, taking into account foreign experience, in the sanctions of Art. 375 of the Criminal Code of Ukraine to provide punishment in the form of deprivation of the right to hold certain positions or to be engaged in certain activity. Suggestions for improving the content of Art. 375 of the Criminal Code of Ukraine have been made, as well as the need to supplement the Criminal Code of Ukraine with the Art. 375-1 "Knowingly unlawful judgment delivered by an arbitrator (arbitrators)" has been pointed out.
Уголовная ответственность за вынесение судьей (судьями) заведомо неправосудного приговора, решения, определения или постановления
Criminal liability of the judge (judges) for delivering knowingly unfair sentence, judgment, ruling or order
Keywords: суддя; вирок; кримінальне правопорушення; покарання; постановлення; судья; приговор; уголовное преступление; наказание; постановления; judge; sentence; criminal offence; punishment; delivery; 343. 91